Genetic diversity and population structure of Plasmodium falciparum in Kenyan–Ugandan border areas. Issue 5 (18th March 2019) - Nderu, David; Kimani, Francis; Karanja, Evaline; Thiong'o, Kelvin; Akinyi, Maureen; Too, Edwin; Chege, William; Nambati, Eva; Wangai, Laura N.; Meyer, Christian G.; Velavan, Thirumalaisamy P.
Summary: Kenya has, in the last decade, made tremendous progress in the fight against malaria. Nevertheless, continued surveillance of the genetic diversity and population structure of Plasmodium falciparum is required to refine malaria control and to adapt and improve elimination strategies. Twelve neutral microsatellite loci were genotyped in 201 P. falciparum isolates obtained from the Kenyan–Ugandan border (Busia) and from two inland malaria‐endemic sites situated in western (Nyando) and coastal (Msambweni) Kenya. Analyses were done to assess the genetic diversity (allelic richness and expected heterozygosity, [ H e ]), multilocus linkage disequilibrium ( I S A ) and population structure. A similarly high degree of genetic diversity was observed among the three parasite populations surveyed (mean H e = 0.76; P > 0.05). Except in Msambweni, random association of microsatellite loci was observed, indicating high parasite out‐breeding. Low to moderate genetic structure ( F ST = 0.022–0.076; P < 0.0001) was observed with only 5% variance in allele frequencies observed among the populations. This study shows that the genetic diversity of P. falciparum populations at the Kenyan–Ugandan border is comparable to the parasite populations from inland Kenya. In addition, high genetic diversity, panmixia and weak population structure in this study highlight the fitness of Kenyan P. falciparum populations to successfully withstand malaria control interventions.